Cxcl9-deficiency attenuates the progression of post-traumatic osteoarthritis in mice - Antonia Donat; Weixin Xie; Shan Jiang; Laura Janina Brylka; Thorsten Schinke; Tim Rolvien; Karl-Heinz Frosch; Anke Baranowsky; Johannes Keller (Inflammation Research, 2025)
Objective Osteoarthritis (OA) is one of the leading causes of disability in the aging population. While about 10% of the adult population is affected by OA, there is to date no curative treatment and joint replacement surgery remains the only option for treating end-stage OA. Previous studies found elevated levels of the chemokine C-X-C motif ligand 9 (CXCL9) in the synovial fluid of OA knees. However, the exact role of CXCL9 in OA progression is still unknown. Methods Female wild-type and Cxcl9 -deficient mice were challenged with a unilateral anterior cruciate ligament transection (ACLT). Joint destruction in early and late stages of experimental OA was assessed using micro-CT scanning, histological scoring, histomorphometry, and gene expression analysis. Results Inactivation of Cxcl9 protected from cartilage destruction and osteophyte formation in post-traumatic OA in mice. Similarly, indices of joint inflammation including synovitis and expression of pro-inflammatory interleukin-1beta were reduced in OA knees of Cxcl9 -deficient mice. However, bone erosion and pathophysiological changes in the subchondral bone compartment remained unaffected in Cxcl9 -deficient mice with experimental OA. Conclusion Our results point towards a pro-inflammatory role of CXCL9 in OA and identify a potential new target for the pharmacological treatment of OA.